Dinâmica de expansão peri-urbana e instrumentos de gestão ambiental sobre áreas protegidas de mananciais no Chile, Brasil e Austrália - Candeias, Flaviana Soares (2022)
Considering the relevance of protected áreas (PAs) used as springs for large urban centers and the pressures they have been suffering with the advancement of urban areas, this work analyzes three PAs and their respective environmental management instruments in different countries of the global southern hemisphere in the Chile, Brazil and Australia, with different socio-environmental and economic realities. The objective is to expand knowledge about the relationship between the variables of land use and the environmental management instruments in force in the area. Through multitemporal mapping of land use, between 1985 and 2020, with LandSat images, Maximum Likelihood classification and in a GIS environment, the changes that occurred in the surroundings and within the limits of the PAs were analyzed. The results indicate a growing urban expansion towards the PAs along with other changes in land use, such as the reduction of vegetation, which influence the quality and quantity of water in springs. Regarding the instruments, problems were identified that converge to inadequate management, in different intensities. To contribute to the maintenance of water resources and ecosystem services in PAs, it is essential that there is an economic investment, monitoring and effective management in the expansion and planning of areas of vegetation linked to urban planning.